Study of Correlation between H. pylori, Life Habits, and Risk Factors among Adult Patients in Gharyan, Libya - Najia Mahdawi,; Ibrahim Karim,; Zainab Abdulazez,; Narjes ALmsagrei,; Najat Alaswad, (AlQalam Journal of Medical and Applied Sciences, 2024)
Helicobacter pylori (H. pylori) is a bacterium that can live in the human stomach and is one of the most common pathogens worldwide. The aim of this study was to evaluate the relationship between H. pylori infection and risk factors and life style habits, such as non-steroidal anti-inflammatory drugs, alcohol ingestion, and smoking. The study was conducted in two centers in Gharyan, Libya (private clinics). The case study took place over three months from July to September 2024 and utilized a validated questionnaire. All participants had confirmed H. pylori infections. A total of 50 cases with positive H. pylori infections were included in this study. They completed the questionnaire and data was analyzed using simple statistics. The questionnaire consisted of three parts. The prevalence of H. pylori infection was higher in females than males in this study. The findings suggested that certain habits, such as perceived stress, frequency of physical activity per week, and duration of physical activity, may influence the presence of H. pylori infection. Additionally, adults with below-normal levels of vitamin D had a higher risk of H. pylori infection. هيليكوباكتر بيلوري هي بكتيريا يمكن أن تعيش في معدة الإنسان وهي أيضًا واحدة من أكثر مسببات الأمراض شيوعًا في العالم. هدف الدراسة الي تقييم العلاقة بين الإصابة بالبكتيريا الحلزونية مع عوامل الخطر والعادات الحياتية مثل مضادات الالتهاب غير الستيرويدية وتناول الكحول وعادات التدخين. أجريت الدراسة في مركزين بمدينة غريان، ليبيا (العيادات الخاصة). تم إجراء دراسة الحالة خلال الأشهر الثلاثة من يوليو إلى سبتمبر 2024 واستخدمت استبيانًا تم التحقق من صحته. تم جمع جميع المشاركين مع عدوى الملوية البوابية الإيجابية. تم جمع 50 حالة في هذه الدراسة وكانت إصابتها إيجابية بالبكتيريا الحلزونية. وأكملت الاستبيان الذي تمت الإجابة عليه واستخدمت إحصائيات بسيطة. وكان الاستبيان يتكون من ثلاثة أجزاء. كان معدل انتشار عدوى الملوية البوابية لدى البالغين بين الإناث أكثر من الذكور في هذه الدراسة. أشارت نتائج هذه الدراسة إلى أن بعض العادات تؤثر على وجود عدوى الملوية البوابية، مثل الإجهاد الملحوظ، وعدد مرات النشاط البدني في الأسبوع، ومدة النشاط البدني. وأيضًا، كان البالغون الذين لديهم مستويات فيتامين د أقل من المعدل الطبيعي أكثر عرضة للإصابة بعدوى الملوية البوابية